Olympics in the time of a pandemic - Dhillon, M. S. (Indian Journal of Orthopaedics, 2020)
Never in history has an Olympic Games been cancelled by a medical issue. The 2020 Tokyo Olympics are now becoming (in)famous for another medical issue; the COVID 19 pandemic, which hangs like a pall of gloom over the event itself. This has led to the postponement of the Olympics to 2021.